Shunt Over-drainage, Slit Ventricle Syndrome, Programmable Valves and Anti-Siphon Devices. A Narrative Review of a Multifactorial and Intractable Problem - Dimitrios Panagopoulos; Georgios Stranjalis; Maro Gavra; Efstathios Boviatsis; Stefanos Korfias (Journal of Integrative Neuroscience, 2022)
The current management strategy of hydrocephalus mainly involves the insertion of a ventriculoperitoneal shunt and is inherently related with a complication widely known as shunt over-drainage. Albeit this is a well-recognized complication, the true incidence and severity of this phenomenon remains undefined and most probably underdiagnosed, necessitating a more comprehensive pathophysiologic and therapeutic consideration. The slit ventricle syndrome is intimately related with the entity of shunt over-drainage, although who’s the definition of the former is implicated by a lack of universally accepted inclusion criteria. Another point of controversy is related with the absence of widely accepted criteria that would be able to discriminate the existing differentiations between these two entities. This is reflected in the fact that there are many proposed, relevant, treatment protocols. The background for all this data is based on the uncertainty and ambiguity regarding the pathophysiological mechanisms that are implicated. Current efforts are centered on the implementation of precautionary measures, as well as on treatment of both of these entities. Currently, there are enough evidence that support the concept that prevention of siphoning via the use of gravitational valves or antisiphon devices is the most efficacious means contained in our current therapeutic armamentarium. We attempt to present an overview of this complex entity, emphasizing on the hydrodynamics of the cerebrospinal fluid circulation in conditions harboring a ventriculoperitoneal shunt, the effect of the siphoning effect and the role of programmable valves and anti-siphon devices in our effort to eliminate this phenomenon. Based on an extensive literature review and on expert opinion, we concluded that the insertion of an anti-siphon device (gravitational shunt valves) could reliably address the issue of over-drainage, when a patient assumes a vertical position. Besides that, there are ongoing prospective studies centered on the safety and efficacy of adjustable gravitational valves, whose results are of ultimate importance. It is of paramount importance to be recognized that, due to the complexity of the pathophysiology of shunted hydrocephalus, lifelong follow-up of patients with ventriculoperitoneal shunts is necessary.